Multi-Combilipases: Co-Immobilizing Lipases with Very Different Stabilities Combining Immobilization via Interfacial Activation and Ion Exchange. The Reuse of the Most Stable Co-Immobilized Enzymes after Inactivation of the Least Stable Ones - Sara Arana-Peña; Diego Carballares; Vicente Cortés Corberan; Roberto Fernandez-Lafuente (Catalysts, 2020)
The lipases A and B from Candida antarctica (CALA and CALB), Thermomyces lanuginosus (TLL) or Rhizomucor miehei (RML), and the commercial and artificial phospholipase Lecitase ultra (LEU) may be co-immobilized on octyl agarose beads. However, LEU and RML became almost fully inactivated under conditions where CALA, CALB and TLL retained full activity. This means that, to have a five components co-immobilized combi-lipase, we should discard 3 fully active and immobilized enzymes when the other two enzymes are inactivated. To solve this situation, CALA, CALB and TLL have been co-immobilized on octyl-vinyl sulfone agarose beads, coated with polyethylenimine (PEI) and the least stable enzymes, RML and LEU have been co-immobilized over these immobilized enzymes. The coating with PEI is even favorable for the activity of the immobilized enzymes. It was checked that RML and LEU could be released from the enzyme-PEI coated biocatalyst, although this also produced some release of the PEI. That way, a protocol was developed to co-immobilize the five enzymes, in a way that the most stable could be reused after the inactivation of the least stable ones. After RML and LEU inactivation, the combi-biocatalysts were incubated in 0.5 M of ammonium sulfate to release the inactivated enzymes, incubated again with PEI and a new RML and LEU batch could be immobilized, maintaining the activity of the three most stable enzymes for at least five cycles of incubation at pH 7.0 and 60 °C for 3 h, incubation on ammonium sulfate, incubation in PEI and co-immobilization of new enzymes. The effect of the order of co-immobilization of the different enzymes on the co-immobilized biocatalyst activity was also investigated using different substrates, finding that when the most active enzyme versus one substrate was immobilized first (nearer to the surface of the particle), the activity was higher than when this enzyme was co-immobilized last (nearer to the particle core).